Co-management strategies for acute myeloid leukemia patients in the community setting - Benton, Christopher; Grunwald, Michael R.; Safah, Hana; Kasner, Margaret (Frontiers in Oncology, 2022)
The treatment landscape for acute myeloid leukemia (AML) has changed substantially in recent years. The introduction of newer therapies, including oral agents, less myelosuppressive agents, and parenteral regimens suitable for outpatient administration, has made it feasible for select patients to receive therapy in the outpatient setting and in community practices. Thorough patient evaluation (including molecular testing), planned supportive care (eg, transfusion support, antimicrobial prophylaxis), and vigilant patient monitoring (for tumor lysis syndrome and adverse events) by a multidisciplinary team are required for successful management of patients both in the community and at specialized leukemia centers. Some patients are unable or unwilling to travel to larger academic centers for treatment, and treatment of AML in the community setting may have potential advantages compared to less conveniently located academic/leukemia centers. This includes reduction of financial hardship for patients and their families and often better opportunities for family/caregiver support. Additionally, partnership between community practices and academic/leukemia centers is often crucial to optimizing AML management for many patients, as collaboration may facilitate access to additional expertise and trials, multidisciplinary teams for supportive care, easier transition to hematopoietic cell transplantation, and access to sophisticated molecular testing. In this review, we discuss AML treatment and management in the community setting, available therapies, and circumstances in which a referral to and co-management with an academic/leukemia center is more strongly recommended.